VIKTIMISASI MAJEMUK (MULTIPLE VICTIMIZATION) ANAK-ANAK KORBAN PERCERAIAN - Reza Indragiri Amriel (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2009)
Divorce is commonly perceived as a traumatic event for children. However, it represents only one form of victimization experienced by children following parental separation. This article argues that children of divorced parents are exposed to three interconnected forms of victimization: the impact of divorce itself, secondary victimization resulting from inadequate judicial mechanisms in child custody decisions, and further victimization caused by parental misconduct, including parental alienation. Using an interdisciplinary normative approach, the study examines child custody from psychological, legal, and Islamic legal perspectives. It concludes that strengthening child-centered judicial mechanisms is essential to ensuring the best interests of the child and preventing repeated victimization.